Kesulitan guru bahasa Inggris dalam mengajar siswa sekolah dasar - Ulfah Khoirotunnisa; Heri Retnawati (Diglosia)
This study investigates the challenges and issues encountered by English language teachers in teaching elementary school students. The aims of this study is to explore the difficulties face by teacher in teaching English to young learners and to identify potential strategies to accomplish these challenges. The research approach that used was a qualitative research design, with in-depth interviews as data collecting method. The participants consisted of ten English teachers. The findings show that teachers face significant obstacles, including difficulties in identifying appropriate teaching materials, methods, strategies, and media that compatible with elementary students’ level. English also frequently perceived by students as a difficult subject, which decrease their learning motivation. Furthermore, inadequate access to teaching resources and limited institutional support are cited as additional barriers. Notably, the study also highlights that the teachers own limited teaching skill and pedagogical competence in English contribute to the overall challenges. In order to overcome these issues, teachers reported engaging in self-directed by joining any professional development activities, such as reading academic journals, attending workshops, and participating in training sessions focused on English language teaching strategies for young learners.